AN ASSESSMENT OF VARIATION IN ACTIVE INGREDIENTS OF AMPUCARE FROM DIFFERENT ZONES OF INDIA (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The present study was designed to assess the variation in curcumin content of Curcuma longa rhizome and total polyphenols in Azadirachta indica bark samples procured from different zones of India. Physico-chemical tests such as total ash, acid insoluble ash, alcohol soluble extractive, water soluble extractive, volatile oil content etc. were also determined. A slight variation was seen in the bark samples of Azadirachta indica. Total ash ranged from 4.25±0.15 (East zone) to 5.57±0.20 (Central zone) whereas acid insoluble ash ranged from 0.80±0.07 (East zone) to 1.52±0.06 (Central zone). Alcohol soluble extractive value of East zone sample was found to be more than 4 times higher 16.95±0.80 than that of central zone 3.85±0.12, where lowest value was recorded. Water soluble extractive value was also found to be highest in East zone sample 17.80±1.10 which was 2 times more than that of Central zone sample 8.45±0.15. This variation may be due to variation in climatic conditions, soil type, pollution stress etc. All the results were within the limits as given in The Ayurvedic Pharmacopoeia of India. Total Polyphenols ranged from 190.0 mgGAE/g of dry weight (Central zone) to 510.0 mgGAE/g of dry weight (East zone). All the samples were found to be rich in total polyphenols. In Curcuma longa samples, Total ash ranged from 3.10±0.20 (South zone) to 4.80±0.25 (North zone) whereas acid insoluble ash ranged from 0.55±0.04 (South zone) to 1.24±0.06 (North zone). Alcohol soluble extractive value was found to be highest in South zone sample 14.80±0.30 which was found to be more than 3 times higher than that of central zone 4.28±0.19 where lowest value was recorded. Water soluble extractive value was also found to be highest in West zone sample 12.55±0.69 and lowest in Central zone sample 8.90±0.37. Volatile oil ranged from 3.50±0.21 North zone sample to 5.50±0.20 South zone sample, where highest volatile oil was recovered. All the results were within the limits as given in The Ayurvedic Pharmacopoeia of India. In our study, curcumin content ranged from 0.30 % (Central zone) to 3.24 % (South zone). Average curcumin content was found to be 1.54 % on dry weight basis. Ampucare is prepared by selection of best quality herbs.